Depression Among Islamic Boarding Schools Students During the COVID-19 Pandemic in East Java, Indonesia - Asri, Yuni; Priasmoro, Dian Pitaloka; Muhtar, Muhammad Solihuddin; Manga, Yankuba B (UI Scholars Hub, 2024)
The COVID-19 pandemic significantly impacts many aspects of life, including health, economy, society, education, and mental well-being. The pandemic impact on mental health, in particular, leads to increased rates of depression, anxiety, and stress. This study aimed to determine the prevalence of depression among Islamic boarding school students in Indonesia and identify factors associated with depression symptoms. This cross-sectional study employed questionnaires for data collection. Assessment of depression levels used the DASS-21 tool. Descriptive statistics and multivariate logistic regression were applied to analyze relationships between variables. The study findings indicated that 62.4% of the students exhibited factors associated with depression. In general, education level, personality type, communication with peers, satisfaction with the living environment, and health status demonstrated significant associations with depression. In conclusion, recognizing and intervening at early stages are crucial for depression prevention and mitigation. This study serves as a key instrument for the policymakers in the field of education, providing insights to promptly take immediate actions, especially regarding the placement of students in Islamic boarding schools in Muslim-majority countries.